Effect of In Ovo Administration of a Multi-Strain Probiotic and Zinc Glycine Chelate on Antioxidant Capacity and Selected Immune Parameters in Newly Hatched Chicks - Artur Ciszewski; Łukasz S. Jarosz; Arletta Bielecka; Agnieszka Marek; Bartłomiej Szymczak; Zbigniew Grądzki; Anna Rysiak (MDPI AG, 2023)
The aim of this study was to determine the effect of in ovo co-supplementation of chicken embryos with a multi-strain probiotic containing effective microorganisms and zinc glycine chelate on total antioxidant capacity; concentrations of sulfhydryl groups, bityrosine bridges, formylkynurenines, hydroperoxides, proteins, corticosterone, pro- and anti-inflammatory cytokines and heat shock proteins; and the activity of catalase and superoxide dismutase in the serum, yolk sac and tissues of broiler chickens at 12 h and at 7 days after hatching. The results indicate high SOD activity in the small and large intestines of chicks at 12 h post-hatch in the groups receiving the multi-strain probiotic and in the small intestine and yolk sac of birds receiving the multi-strain probiotic and Zn-Gly chelate. High concentrations of TNF-α and IFN-γ in the yolk sac and serum after in ovo administration of Zn-Gly chelate were observed 12 h after hatching. The use of a probiotic and a probiotic with Zn-Gly chelate increased the total antioxidant capacity in the tissues of chickens. It can be concluded that in ovo administration of a multi-strain probiotic and Zn-Gly chelate can maintain the oxidant/antioxidant balance in chickens and increase the defense capacity against oxidative stress.